Comparative impacts of nitrogen, sulfur, and zinc fertilization on grain yield, protein content, antioxidant capacity and its loss during polishing process among rice varieties - Sangnak, Sunitha; Veeradittakit, Jeeraporn; Prom-u-thai, Chanakan (Frontiers in Agronomy, 2026)
Increasing grain protein in rice through fertilizer management during cultivation is a promising approach to address protein deficiency, particularly in populations where rice is the staple food and access to high-protein foods is limited. This study aimed to compare the impacts of fertilizer management (control, N, S, and Zn) on grain yield, protein content, and antioxidant capacity among four rice varieties (KDML105, PTT1, KDK, and K4) under field condition for four replicates. The rice varieties responded differently to fertilizer management in terms of grain yield, protein content, and antioxidant capacity. Applying all fertilizers increased grain yield in all varieties compared with the control, although the magnitude of increase varied among varieties. The highest grain protein content in unpolished rice was observed with N fertilizer application across all varieties, while S and Zn had a smaller effect. A similar trend was found in polished rice at both 20 and 60 s of polishing, suggesting increased protein content in both the outer and inner grain layers. Fertilizer treatments increased grain nutrient concentrations but tended to have a negative impact on grain yield. Antioxidant capacity in both unpolished and polished grains was also influenced by fertilizer applications and showed a positive correlation with grain protein content, indicating a potential dual benefit for human health through improved protein and antioxidant intake. These results provide essential insights for optimizing fertilizer management to enhance both yield and high nutritional values in rice production systems.